Inovasi Kemandirian Keluarga untuk Mendukung Ketahanan Pangan: Pakan Ternak Ayam - Wiliyanti, Vandan; Al-Rafi, M.; Fitriyana, Almaratul; Anggraini, Elen Dea; Ramadania, Faisya; Nurohman, Idhar; Jamiatun, Jamiatun; Fatimah, Julita Ripma; Taufiqqurahman, Moh Adek; Kimlie, Sesilia Wulan (Abdimas Indonesian Journal, 2024)
Food security an important issue like affects the quality of human resources and social stability of a country. As an archipelagic country that depends on the agriculture, plantation, fisheries, and livestock sectors, Indonesia still faces challenges in meeting the food needs of animal protein sources, especially from chickens. Although purebred chicken production dominates, its dependence on imports makes it vulnerable. Meanwhile, free-range chickens have great potential, but are limited by low productivity and high mortality rates. This research aims to develop innovations in the maintenance of free-range chickens to support family food security. method used is Participatory Action Research (PAR), involves the initial mapping stages, determining action solutions, and implementing actions. The main activities are seminars and socialization with the theme "Family Independence Innovation to Support Food Security" in Pasemah Vilage. Results is  show that a participatory approach can involve the community in developing efficient and sustainable animal feed methods. Socialization about making chicken feed from local ingredients and household waste succeeded  increasing the knowledge and skills of participants. The implementation of this knowledge by the community has the potential to reduce dependence on commercial feed and increase food independence at the household level. In conclusion, innovations in free-range chicken rearing and local feed production can be an effective strategy to increase family food security, encourage independence, and support local economic development in Sinar Pasemah Village.